Luminescence of Cr3+/Yb3+ co-doped oxyfluoride silicate glasses for crystalline silicon solar cell down-conversion devices. Issue 10 (July 2020) - Fu, Wenbin; Zhang, Chaomin; Li, Zhangwen; Xia, Jinan; Ping, Yunxia
Abstract: Oxyfluoride silicate glasses co-doped with Cr 3+ and Yb 3+ ions were fabricated in this work. High △T (178–214 °C) value demonstrated that the thermal stability of the prepared glasses were better than tellurite and germanate glasses. X-ray diffraction (XRD) curves proved the amorphous nature of the glasses, the energy dispersive spectroscopy (EDS) analysis and Fourier Transform infrared spectroscopy (FT-IR) curves explored the network structure of glasses. The photoluminescence excitation (PLE) and photoluminescence emission (PL) spectra show that the glasses absorption peaks located at 430 nm (Cr 3+ : 4 A2g - 4 T1g (P)) and 627 nm (Cr 3+ : 4 A2g - 4 T2g ), while the emission peak close to 1010 nm (Yb 3+ : 2 F5/2 - 2 F7/2 ), which meets the condition of energy down-conversion. Besides, the energy transfer efficiency (ηCET  = 33.5%) and the quantum cutting efficiency (ηQE  = 133.5%) were calculated from the measured decay curves. These values were higher than Cr 3+ /Yb 3+ co-doped fluorosilicate glass with incorporating of CaF2 (21.5% and 123.5%) and Tb 3+ /Yb 3+ oxyfluoride glass (13.5% and 113.5%), indicating the prepared samples are conducive to the energy transfer from Cr 3+ to Yb 3+ ions. The experimental results reveal that the oxyfluoride silicate glasses have potential application prospects in crystalline silicon (c-Si) solar cells.